The Growth of Seed Derived Onion on Various Strenght of MS Medium and BAP (Benzyl Amino Purine) Concentrations - W. Munandar, Eka Handayani; Basri, Zainuddin; Maemunah, Maemunah (Universitas Tadulako, 2021)
The growth of explant in culture media is affected by a number of factors, including the strength of basal media and the concentration of plant growth regulators added into culture media. Experiments were conducted in two steps; the aim of the first experiment was to obtain a suitable strength of MS medium for the growth of onion seeds and the aim of the second experiment was to obtain an appropriate BAP concentration for each strength of MS medium for the growth of seed derived onion shoots. The first experiment was designed in Completely Randomized Design (CRD) with one factor, with treatment tested namely the strength of MS medium in two levels, eg. a half strength of MS medium and full strength of MS medium. The second experiment was also designed in CRD with factorial pattern; treatments tested were the strength of MS medium as the first factor consisted of two levels, namely a half strength of MS medium and full strength of MS medium; and the concentration of BAP as the second factor which consisted of four levels, namely 1 mg/l, 2 mg/l, 3 mg/l and 4 mg/l BAP. Results of these experiments showed that a half strength of MS medium was suitable for the growth of onion seeds which was indicated by the percentage of seed germination upto 100% and the formation of leaves tended to be more intensive. Culture medium supplemented with 4 mg/l BAP was appropriate for the growth of seed derived onion shoots which was reflected by the formation of intensive leaves and roots, in average 2.58 leaves per exsplant and 8.75 root hairs per exsplant, respectively.